2008
DOI: 10.1002/jnr.21726
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous tumor necrosis factor‐α rapidly alters synaptic and sensory transmission in the adult rat spinal cord dorsal horn

Abstract: The proinflammatory cytokine tumor necrosis factor-alpha (TNF-alpha) is involved in the generation of inflammatory and neuropathic pain. This study investigated if TNF-alpha has any effect on spinal synaptic and/or sensory transmission by using whole-cell recordings of substantia gelatinosa (SG) neurons in transverse lumbar spinal cord slices of adult rats and by using behavioral tests. After intrathecal administration of TNF-alpha in adult rats, spontaneous hind paw withdrawal behavior and thermal hyperalgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 51 publications
6
46
1
Order By: Relevance
“…TNF causes a rapid exocytosis of AMPA receptors in hippocampal pyramidal neurons [125]. Rapid synaptic effects of TNF, within minutes, were reported in 2008 in an experimental rat spinal cord model [114]. More recently, even more rapid synaptic effects of TNF have been reported [110,112].…”
Section: Rapid Clinical Responsementioning
confidence: 99%
See 2 more Smart Citations
“…TNF causes a rapid exocytosis of AMPA receptors in hippocampal pyramidal neurons [125]. Rapid synaptic effects of TNF, within minutes, were reported in 2008 in an experimental rat spinal cord model [114]. More recently, even more rapid synaptic effects of TNF have been reported [110,112].…”
Section: Rapid Clinical Responsementioning
confidence: 99%
“…• Inhibition of long-term potentiation [56,59,60,162] • Modulation of AMPA and GABA receptors [125] • Control of synaptic strength [123] • Modulation of synaptic scaling [124] • Modulation of synaptic transmission by gliotransmission [13][14][15] • Rapid alteration of synaptic transmission in the spinal cord dorsal horn [114] • Rapid modulation of enzymes (nSmase2) (within seconds) involved in NMDA trafficking [110] Review Perispinal etanercept: a new therapeutic paradigm in neurology and disability, even in patients presenting with years of severe, intractable pain [23,24]. In a 143-patient, open-label study, rapid improvement (within 20 min) and significant and sustained reductions in pain, sensory disturbance and weakness were documented in a patient population with an average pain duration of 9.8 years [44].…”
Section: Rapid and Sustained Clinical Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal neuroinflammation in peripheral neuropathy is characterized by activation of microglia and astrocytes, as well as upregulation of the proinflammatory mediator, tumor necrosis factor-α (TNF-α) [8, 13, 14]. Microglia and astrocytes synthesize TNF-α [15], and TNF-α contributes to neuropathic pain [16, 17]. Additionally, inhibiting activation of microglia and astrocytes [1820], as well as spinal TNF-α [21] have analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…A␦ fibers mediate first, sharp pain, and C fibers mediate second, burning pain (Torebjork and Hallin 1973). Several studies have found similar modulations on A␦ and C fiber-mediated synaptic transmission by various neuromodulators (Lao et al 2004;Youn et al 2008), whereas other studies have found different modulations (Ataka et al 2000;Ikoma et al 2007;Ito et al 2000).…”
mentioning
confidence: 96%